Legal Protection For Online Transportation Partners: a Comparison Between Indonesia and Malaysia in The Implementation of Social Protection Systems - Ninne Zahara Silviani; Evy Evy; Febri Jaya; Nur Fatihah; Rufinus Hotmaulana Hutahuruk (QONUN: Jurnal Hukum Islam dan Perundang-undangan, 2026)
This study seeks to examine and critically analyze the legal protection afforded to online transportation partners in Indonesia and Malaysia, with particular emphasis on identifying regulatory gaps within the existing social protection frameworks. The primary issue stems from the inadequacy of Law No. 13 of 2003 on Manpower in addressing the legal status of online transportation drivers, as the prevailing working arrangements do not conceptually satisfy the essential elements of an employment relationship as defined under the law. This condition gives rise to legal uncertainty concerning access to social security, occupational safety guarantees, and income protection for online transportation partners. This study adopts a normative juridical approach, employing both statutory and comparative legal analyses. The findings reveal that Malaysia has established a more structured and systematic framework for integrating platform-based workers into formal social protection schemes. In contrast, Indonesia continues to experience a regulatory gap, resulting in heightened vulnerability of workers to occupational risks and restricted access to comprehensive social protection mechanisms. This study concludes that Indonesia might to adapt aspects of Malaysia’s labor policies as a reference, through regulatory harmonization, strengthening the role of the government, and providing sustainable social protection programs.